Theoretical perspectives of trait anxiety: A systematic review - P. Bijulakshmi; V. Veera Balaji Kumar (Current Medicine Research and Practice)
Background: Anxiety has been extensively studied since the Freudian era as an essential factor in the development of psychopathology. This study explored theoretical models of trait anxiety, a concept introduced by Spielberger in 1983, distinguishing between trait and state anxiety. Trait anxiety reflects a predisposition to anxiety, whereas state anxiety is a reaction to stressors. Aim: This study aimed to review the existing literature on the theoretical models of trait anxiety. Materials and Methods: ‘Theoretical models of trait anxiety’ were typed using Google and PubMed to retrieve articles. The inclusion criteria included full-length articles and observational and interventional studies that explored theoretical models. The exclusion criteria included studies unrelated to theoretical models or lacking implications. Studies with no impact on the theoretical models were excluded. Results: Of the 174 initially selected articles, 71 met the inclusion criteria. The sample was divided into two groups: Group A, which explained various trait anxiety theories (17 articles), and Group B, which evaluated these concepts (54 articles). The studies span the period 1984–2023. Group A emphasised the multi-directional model, highlighting the interplay of genetic, cognitive, physiological and behavioural factors in trait anxiety development. Group B findings suggest that while genetics contributes to high trait anxiety propensity, its manifestations are primarily behavioural, especially under high state anxiety. Cognitive processes, such as attentional biases and specific brain area stimulation, intensify reactions in individuals with high-trait anxiety during low-state anxiety situations. Conclusions: In conclusion, this systematic review indicates widespread acceptance of the four-factor theory in trait anxiety models. Both observational and interventional studies support the significant role of physiological and cognitive processes in the development of trait anxiety.